Risk of cryptorchidism among sons of horticultural workers and farmers in Denmark - Jørgensen, Kristian Tore; Jensen, Morten Søndergaard; Toft, Gunnar Vase; Larsen, Ann Dyreborg; Bonde, Jens Peter; Hougaard, Karin Sørig (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'Previous studies indicate an increased risk of cryptorchidism, incomplete testicular descent, among sons of women working with pesticides. This study assessed the risk of cryptorchidism among boys of parents employed as horticultural workers and farmers using nationwide registers on occupation and cryptorchidism. ' ' METHODS ': 'The cohort consisted of >600 000 boys born in Denmark from 1980–2007 with a parent in employment during pregnancy. These boys were followed for cryptorchidism from 1980–2009 comparing risks among sons of horticultural workers and farmers with sons of parents in other occupations. Hazard ratios (HR) and 95% confidence intervals (95% CI) were estimated using Cox regression adjusting for parental age, birth years, parity, and geographical region. ' ' RESULTS ': 'Sons of maternal farmers were at increased risk of cryptorchidism (157 cases; HR 1.31, 95% CI 1.12–1.53) compared to boys of mothers in other occupations (15 511 cases). Paternal occupation as farmer was unrelated to the risk among sons. Maternal occupation as a horticultural worker was associated with a non-significantly increased risk (72 cases; HR 1.20, 95% CI 0.95–1.52). A similar association was found for paternal horticultural workers. Sons of maternal farmers or horticultural workers who likely worked in the first trimester were not at increased risk of cryptorchidism. ' ' CONCLUSIONS ': 'This nationwide cohort study found a slightly increased risk of cryptorchidism in sons of maternal horticultural workers and farmers. However, subgroup analyses indicated similar findings for paternal horticultural workers, and no association for women likely working in the first trimester. The main findings should therefore be interpreted with caution.
Keywords: cohort study; cryptorchidism; Denmark; farmer; farming; horticultural worker; horticulture; occupational exposure; orchiopexy; pesticide